2018
DOI: 10.1038/s41598-018-23101-2
|View full text |Cite
|
Sign up to set email alerts
|

Climate change effect on wheat phenology depends on cultivar change

Abstract: Changing crop phenology is considered an important bio-indicator of climate change, with the recent warming trend causing an advancement in crop phenology. Little is known about the contributions of changes in sowing dates and cultivars to long-term trends in crop phenology, particularly for winter crops such as winter wheat. Here, we analyze a long-term (1952–2013) dataset of phenological observations across western Germany and observations from a two-year field experiment to directly compare the phenologies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 36 publications
(47 reference statements)
1
60
0
3
Order By: Relevance
“…Adaptation strategies for the agricultural sector will need to address concurrent water‐stress conditions throughout Europe. Negative effects of the projected increase in extremes might be only partially limited by shorter phenological cycles, new varieties, and fertilization effects of increased atmospheric CO 2 concentration (Challinor et al, ; Kimball, ; Obermeier et al, ; Parkes et al, ; Rezaei, Siebert, Hüging, et al, ; Trnka et al, ). Crops, such as maize, could be more affected by projected increases in severe drought events (Webber et al, ; Zampieri et al, ), and as seen in 2018, the livestock sector will also be negatively impacted due to the lack of fodder crops.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptation strategies for the agricultural sector will need to address concurrent water‐stress conditions throughout Europe. Negative effects of the projected increase in extremes might be only partially limited by shorter phenological cycles, new varieties, and fertilization effects of increased atmospheric CO 2 concentration (Challinor et al, ; Kimball, ; Obermeier et al, ; Parkes et al, ; Rezaei, Siebert, Hüging, et al, ; Trnka et al, ). Crops, such as maize, could be more affected by projected increases in severe drought events (Webber et al, ; Zampieri et al, ), and as seen in 2018, the livestock sector will also be negatively impacted due to the lack of fodder crops.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is more likely due to the limitation of models in accurately representing heat stress influence, such as slow updates of key parameters related to heat and drought resistance and lack of explicitly accounting for heat stress effect during the development stages of different maize cultivars. Rezaei, Siebert, Hüging, and Ewert () also found that ignoring cultivar changes in analyses of historic changes in phenology leads to an overestimate of the temperature sensitivity of the phenology of winter wheat in Germany. A similar model parametrization bias may exist in other crops, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, cultivars that are selected in hot climates are less sensitive to yield losses (Butler & Huybers, ), a feature that is not reflected in the GGCMs. Rezaei et al () suggest that the temperature response in phenology could be flawed by not accounting for changes in cultivar choice in the historic past. Also, Zhu et al () find that GGCMs often overestimate the response in growing period length compared to other yield‐reducing effects of warming.…”
Section: Discussionmentioning
confidence: 99%